2010
DOI: 10.1029/2010jb007579
|View full text |Cite
|
Sign up to set email alerts
|

InSAR data as a field guide for mapping minor earthquake surface ruptures: Ground displacements along the Paganica Fault during the 6 April 2009 L'Aquila earthquake

Abstract: , a moderate earthquake (M w = 6.3; M l = 5.8) struck the Abruzzo region in central Italy, causing more than 300 fatalities and heavy damage to L'Aquila and surrounding villages. Coseismic surface effects have been thoroughly documented by timely field surveys as well as by remote sensing analyses of satellite images. The outstanding quality of geological, seismological, geodetic, and interferometric synthetic aperture radar (InSAR) information arguably represents the best ever data set made available immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 33 publications
5
39
0
Order By: Relevance
“…All coseismic displacements are compatible with those predicted by a shallow planar SW-dipping normal fault with a ∼0.5 to 0.6 m coseismic slip, proposed by various authors (Anzidei et al, 2009;Atzori et al, 2009;Walters et al, 2009Cheloni et al, 2010Guerrieri et al, 2010;Serpelloni et al, 2012) on the basis of the dislocation theory in an elastic half-space (Okada, 1985).…”
Section: Coseismic and Postseismic Effects Of The April 6 2009 L'aqusupporting
confidence: 78%
See 1 more Smart Citation
“…All coseismic displacements are compatible with those predicted by a shallow planar SW-dipping normal fault with a ∼0.5 to 0.6 m coseismic slip, proposed by various authors (Anzidei et al, 2009;Atzori et al, 2009;Walters et al, 2009Cheloni et al, 2010Guerrieri et al, 2010;Serpelloni et al, 2012) on the basis of the dislocation theory in an elastic half-space (Okada, 1985).…”
Section: Coseismic and Postseismic Effects Of The April 6 2009 L'aqusupporting
confidence: 78%
“…13.42 • ). The focal mechanism (Pondrelli et al, 2010), aftershock distribution (Chiarabba et al, 2009) and surface deformation (e.g., Anzidei et al, 2009;Atzori et al, 2009;Cheloni et al, 2010;Falcucci et al, 2009;Guerrieri et al, 2010) indicate that this shallow event occurred on a NW-SE trending SW-dipping normal fault, probably propagating to the surface at the Paganica fault.…”
Section: Introductionmentioning
confidence: 98%
“…Cinti et al, 2011;Galli, Giaccio, Messina, Peronace, & Zuppi, 2011;Gori et al, 2012;Improta et al, 2012;Moro et al, 2013). At the same time, despite this proliferation of investigations, (Blumetti, Guerrieri, & Vittori, 2013;Civico, Pucci, De Martini, & Pantosti, 2014;Galli et al, 2010;Giaccio et al, 2012;Guerrieri et al, 2010), these are limited from a long-term geological perspective.…”
Section: Introductionmentioning
confidence: 99%
“…However, Fujiwara et al (2000a, b), Fukushima et al (2013), Guerrieri et al (2010), Nishimura et al (2008) and Wei et al (2011) reported that lineaments representing small displacements appear on interferograms, and Oskin et al (2012) reported that small displacements appear in differential LiDAR images.…”
Section: Introductionmentioning
confidence: 99%